Efficacy and mechanism of action of intrahippocampalD-cycloserine in an animal model of Posttraumatic Stress Disorder (PTSD) - Fairbairn, Lorren Rosli (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.